Relationship between Maximum Phonation Time (MPT) and age and teaching experience in female teachers with and without voice complaints working in primary schools of Tehran, Iran - Ozra Aghadoost; Younes Amiri Shavaki; Negin Moradi; Shohreh Jalai (Vesnu Publications, 2013)
Introduction: Teachers comprise the largest group of professional voice users. It seems that they are more susceptibleto voice disorders than other groups of users. The purpose of this study was to determine and comparethe maximum phonation times (MPTs) offemale elementary-school teachers with and without voice complaint. It was also aimed at determining the effect of age and teaching experience on the MPT in this population. Materials and Methods: Eighty female teachers, who participated in this cross-sectional descriptive- analytical study, were divided into two group's ofsubjects with and without voice complaints. After takingeach subject's historythrough interviewing, allparticipants were asked to take a deep breath and sustainthe vowel /a/ for as long aspossible. Theywere requested to repeatthis task three times with 1-minute restintervals between the trials.Thelongest durationwas considered as the maximum phonation time. Results: Themean of MPT in group with voice complaints (88.2 ± 88.12) was significantly differentfrom that of subjects without any voice complaints (17.3 ± 97.15) (P > 0.05). Moreover, age and teaching experience hada significant negative correlation with MPT in both groups. Conclusion: The results of this study indicated that as the age and teaching experience increased, the mean of MPT reduced in all subjects regardless of having any voice complaint or not. Also, the mean of MPT was significantly lower in the group with a voice complaint than in the group without it. Keywords: Maximum phonation time (MPT), Voice complaint, Female teacher, Elementary school